THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE ON EARNINGS QUALITY WITH GOOD CORPORATE GOVERNANCE (GCG) AS A MODERATING VARIABLE IN STATE-OWNED ENTERPRISES (SOES) LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2018 – 2022 PERIOD - Mochamad Revan Adzani Putra; Vannesa Edellweis; Hery Syaerul Homan (Universitas La Tansa Mashiro, 2024)
The purpose of this research was to determine the effect of Corporate Social Responsibility (CSR) on earnings quality with Good Corporate Governance (GCG) as a moderating variable in State-Owned Enterprises (BUMN) companies listed on the Indonesia Stock Exchange (IDX) for the 2018 – 2022 period. The method used in this research is a quantitative method with a descriptive verification approach with secondary data obtained from financial reports and sustainability reports. The population in this study were 24 BUMN companies listed on the IDX for the period 2018-2022. The sampling technique used was purposive sampling with the results of 17 sample companies. The data analysis technique used is panel data regression analysis. The results of this study indicate that Corporate Social Responsibility (CSR) has an effect on earnings quality, but Good Corporate Governance (GCG) cannot moderate the relation between Corporate Social Responsibility (CSR) and earnings quality. Keywords: Corporate Social Responsibility (CSR), Earning Quality, Good Corporate Governance (GCG).